Metagenome Skimming of Insect Specimen Pools: Potential for Comparative Genomics - Linard, Benjamin (Genome Biol Evol, 2015)
Metagenomic analyses are challenging in metazoans, but high-copy number and repeat regions can be assembled from low-coverage sequencing by “genome skimming,” which is applied here as a new way of characterizing metagenomes obtained in an ecological or taxonomic context. Illumina shotgun sequencing on two pools of Coleoptera (beetles) of approximately 200 species each were assembled into tens of thousands of scaffolds. Repeated low-coverage sequencing recovered similar scaffold sets consistently, although approximately 70% of scaffolds could not be identified against existing genome databases. Identifiable scaffolds included mitochondrial DNA, conserved sequences with hits to expressed sequence tag and protein databases, and known repeat elements of high and low complexity, including numerous copies of rRNA and histone genes. Assemblies of histones captured a diversity of gene order and primary sequence in Coleoptera. Scaffolds with similarity to multiple sites in available coleopteran genome sequences for Dendroctonus and Tribolium revealed high specificity of scaffolds to either of these genomes, in particular for high-copy number repeats. Numerous “clusters” of scaffolds mapped to the same genomic site revealed intra- and/or intergenomic variation within a metagenome pool. In addition to effect of taxonomic composition of the metagenomes, the number of mapped scaffolds also revealed structural differences between the two reference genomes, although the significance of this striking finding remains unclear. Finally, apparently exogenous sequences were recovered, including potential food plants, fungal pathogens, and bacterial symbionts. The “metagenome skimming” approach is useful for capturing the genomic diversity of poorly studied, species-rich lineages and opens new prospects in environmental genomics.